2016
DOI: 10.1038/srep21228
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 Modulates Myocardial Hypertrophic Response Induced by Angiogenesis in Heart

Abstract: Myocardial hypertrophy is an adaptive response to hemodynamic demands. Although angiogenesis is critical to support the increase in heart mass with matching blood supply, it may also promote a hypertrophic response. Previously, we showed that cardiac angiogenesis induced by placental growth factor (PlGF), promotes myocardial hypertrophy through the paracrine action of endothelium-derived NO, which triggers the degradation of regulator of G protein signaling 4 (RGS4) to activate the Akt/mTORC1 pathways in cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Furthermore, a 3′ UTR-containing fragment of mouse BCAT2 was amplified and cloned into the luciferase reporter plasmid to detect the luciferase activity. The luciferase activity was significantly downregulated by miR-182 ( Figure 6C ), consistent with the results of a previous report (Li et al, 2016). Meanwhile, protein levels of BCAT2 were significantly decreased in cortical neurons overexpressing miR-182 ( Figure 6D ), but the expression of BCAT2 increased when blocking the endogenous miR-182 by the inhibitor ( Figure 6E ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, a 3′ UTR-containing fragment of mouse BCAT2 was amplified and cloned into the luciferase reporter plasmid to detect the luciferase activity. The luciferase activity was significantly downregulated by miR-182 ( Figure 6C ), consistent with the results of a previous report (Li et al, 2016). Meanwhile, protein levels of BCAT2 were significantly decreased in cortical neurons overexpressing miR-182 ( Figure 6D ), but the expression of BCAT2 increased when blocking the endogenous miR-182 by the inhibitor ( Figure 6E ).…”
Section: Resultssupporting
confidence: 92%
“…We found that BCAT2 expression was significantly downregulated by miR-182 ( Figure 6B ). BCAT2 is known to be a target of miR-182 in PIGF mice and mouse embryonic fibroblasts (Li et al, 2016). Furthermore, a 3′ UTR-containing fragment of mouse BCAT2 was amplified and cloned into the luciferase reporter plasmid to detect the luciferase activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can act as an oncogene in several types of cancers [32,33]. Only a few previous studies investigated the functions of miR-182 in the heart, which indicated that miR-182 was related to cardiac hypertrophy [34,35]. In addition, a previous study showed that miR-182-5p could protected H9c2 cells from hypoxia-induced apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…PLSR analysis gave quantitative outputs to how likely each microRNA was involved in our response. Certain microRNA’s identified by our anaylsis have been shown to regulate important function like fibrosis (miR-27a and miR-29c 26, 27 ), cardiac hypertrophy (miR-29c 28 , miR-96 29, 30 , miR-182 31, 32 and miR-185 33 ), angiogenesis (miR-27a 34 ), and apoptotsis (miR-138 35, 36 , miR-25 37 ). Although, our model is predictive of microRNA-based mechanism, these targets still need to be validated in the future studies.…”
Section: Discussionmentioning
confidence: 93%